Implementing project-based learning to enhance communicative skills in 4th grade students with autism in Cotopaxi province - Coello Jiménez, Hugo Fabrizio; Collaguazo Potosí, Alicia Magdalena; Sánchez Vargas, Araceli Margoth; Riera Hermida, Fernando Patricio (Arandu UTIC, 2025)
This research was conducted in a public school in the province of Cotopaxi, Ecuador. The main objective was to explore how project-based learning could improve communication skills in autistic students in 4th grade of primary school. The participants were a group of students aged 7 to 8 years, where there were two students with autism spectrum disorder. Project-based learning was a fundamental aspect during this teaching process because it allowed the students to improve interaction with their peers and with the English teacher. The students' English level proficiency was pre-A1 according to the results of the diagnostic test carried out at the beginning of the school term. Data were collected through the observation as a qualitative instrument and pre-test, post-test, and rubric as a quantitative instrument. As a final result, the data showed that autistic participants improved their communication skills from 0.70 at the beginning of the study and after the implementation of the project they finished with 2.69 on a scale of 1 to 5, demonstrating that project-based learning has the potential to develop the communicative skills.